Ewing Sarcoma Family Tumors: Past, Present and Future Prospects - Abbas, Adil; Alaa, Mohammed N.S. (Current Cancer Therapy Reviews, 2021)
Ewing’s sarcoma (ES), also known as mesenchymal primitive neuroectodermal tumor (PNET), is a malignant round blue cell tumor (MRBCT) with a varying degree of neuronal differentiation. PNET arises from the primitive nerve cells of the central nervous system (CNS) but may also occur in the bones of the extremities, pelvis, vertebral column, and chest wall. Extraskeletal ES/PNET may affect the various soft tissues, including those of the pelvis, paraspinal region, and thoracopulmonary region. Histopathological differentiation between ES, PNET, and other related sarcomas is often difficult. On light microscopy, the same histopathological appearance of ES has been termed PNET, Askin- Rosay (A-R) tumor, and malignant neuroepithelioma by various other authors. The immunohistochemical distinction is also difficult due to poor tissue differentiation and low intake of the various specific immunohistochemical markers. The most frequent translocation is t (11; 22) (q24; q12), resulting in the EWSR1-FLI1 fusion gene detected in nearly 90% of cases and is considered the hallmark of the diagnosis of ES, PNET, atypical ES, and A-R tumor. Therefore, ES, atypical ES, PNET, and A-R tumor are currently regarded as one entity grouped together under the Ewing Family Tumor (EFT) and are treated in an identical way. EFT represents only about 3% of all pediatric malignancies. The annual incidence is between 2 and 5 cases per million children per year. The peak prevalence of the tumor is between the ages of 10 and 15 years. The incidence is higher in males than in females, with a ratio of 1.3:1. Newer groups of MRBCT that have great similarities to EFT are being recently described. These tumors, atypical EFT and Ewing’s like Sarcomas (ELS), bear similarities to EFT but have basic morphological and molecular differences. Optimal treatment requires the use of adjuvant and new-adjuvant chemotherapy (CTR), radical surgical resection and/or involves field radiotherapy (RT). The reported disease-free survival (DFS) and overall survival (OS) range between 45-80% and 36-71%, respectively. The overall prognosis for the metastatic and recurrent disease remains poor. The use of newer conventional and targeted medications, improved RT delivery, and surgical techniques may further improve the outcomes. The past few years have seen advances in genomics-based sarcoma diagnosis and targeted therapies. In this comprehensive review article, we provide a detailed report of EFT and discuss the various clinical aspects and the recent advances used in the diagnosis and treatment.
Keywords: EWSR1-FLI1 gene fusion